Writing from A to Z : (McGraw-Hill, 2005)
This book is designed as a textbook for a writing class with print as well as online content. It includes topics such as basic grammar, logic and argumentation, methods of development, and sample student papers.You'll notice right away it is geared for the teacher, with notes on how to address topics with students and how to handle class sort of issues. If you webmaster a writing blog, you might find this especially--and unusually--helpful as a way of organizing content and covering relevant topics for your readers and viewers.